Association Between Kinetics of Early Biofilm Formation and Clonal Lineage in Escherichia coli - Flament-Simon, Saskia-Camille; Duprilot, Marion; Mayer, Noémie; García, Vanesa; Alonso, María Pilar; Blanco, Jorge; Nicolas-Chanoine, Marie-Hélène (Frontiers in Microbiology, 2019)
Background. Escherichia coli biofilm formation has mostly been assessed in specific pathogenic E coli groups. Here, we assessed the early biofilm formation (EBF), i.e. adhesion stage, using the BioFilm Ring Test® on 394 E. coli clinical isolates (EC) [196 consecutively isolated (CEC) in 2016 and 198 ESBL-producing E. coli (ESBLEC) isolated in 2015]. Then, biofilm-forming ability was contrasted with phylogroups, clonotypes (fumC-fimH) and sequence types (ST), all being used to define clones, virulence factors (VF) and FimB. Result. According to both biofilm production levels at 2h, 3h and 5h, and EBF kinetics over 5h, CEC and ESBLEC isolates segregated into three EBF groups: strong (G1), moderate (G2) and weak (G3) producers. At 2h, strong producers were more frequent among CEC (n=28; 14.3%) than among ESBLEC (n=8; 4%) P=0.0004). As CEC and ESBLEC isolates showed similar individual EBF kinetics in each group, comparison of isolate features between each group was applied to gathered CEC and ESBLEC isolates and after 2h incubation, 2h being the most representative point time of the CEC and ESBLEC isolate segregation into the three groups. Phylogroup B2 displayed by 51.3% of the 394 isolates was more frequent in G1 (77.8%) than G3 (47.6%) (P=0.0006). The 394 isolates displayed 153 clones of which 31 included at least three isolates. B2-CH14-2-ST127, B2-CH40-22-ST131, B2-CH52-5/14-ST141 and E-CH100-96-ST362 clones were associated with G1 (P<0.03) and accounted for 41.7% of G1 isolates. B2-CH40-30-ST131 clone was associated with G3 (P<0.0001) and accounted for 25.5% of G3 isolates. VF mean was higher among G1 than among G3 isolates (P<0.001). FimB-P2 variant was associated with G1 (P=0.0011) and FimB-P1 variant with G3 (P=0.0023). Clone, some VF, and FimB were associated with EBF, clonal lineage being able to explain 72 % of the variability of EBF. Conclusion. Among our 394 isolates, <10% are able to quickly and persistently produce high biofilm levels over 5h. These isolates belong to a few clones previously described in various studies as dominant gut colonisers in mammalians and birds and comprised B2-CH40-22-ST131clone i.e. the ancestor of the globally disseminated B2-CH40-30-ST131 clone that is the dominant clone among the weak biofilm producers.